MANAJEMEN STRATEGIK DAN MANAJEMEN OPERASIONAL SERTA IMPLEMENTASINYA PADA LEMBAGA PENDIDIKAN - Mappasiara Mappasiara (Universitas Islam Negeri Alauddin Makassar, 2018)
Education is a long-term investment in designing the pattern of human life in the future. First, education as an effort oriented to the formation of a potential human figure intellectually through the learning process; Secondly, education is an ethnically and ethnically formative society through the transfer of values process contained therein; Third, education is one of the guarantees to gain a better life as well as high dignity. In order for education to be an investment then the development and dynamics of educational institutions to a better direction is a necessity. One of the theoretical concepts offered in this paper is the implementation of strategic management and operational management in educational institutions. Through these two theoretical concepts, management of educational institutions is expected to direct and influence the quality of education products / outcomes such as curriculum, administration of institutional management and students.